Liming on dry matter yield and mineral composition of sarghum in a Low Humic Gley soil. - Paula, Miralda Bueno de; Nogueira, Francisco Dias; Santos, Hélio Lopes dos (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out in greenhouse to study the effects of liming on dry matter yield and nutrient concentration in grain sorghum (Sorghum graniferum (L.) Moench AG 1003 in a Low Humic Gley (LHG) soil, rich in organic matter. The treatments consisted of five levels of liming, with two recommendation methods: control (without liming); liming by the changeable Al (2 x Al) + 2 - (Ca + Mg) method, and 1/3, 2/3 and 4/3 of liming recommended by the pH 6.0 Shoemaker, McLean & Pratt method. Adequate P levels in the tissue of the plants were obtained with higher levels of liming than those indicated by the Al and Ca + Mg method. With liming application by the Al method, only 36% of the exchange Al was neutralized. The maximum yields of root and leaf dry matter were obtained with liming levels higher than those indicated by the Al and Ca + Mg method. The results indicate that the Al and Ca + Mg method was not a good criterium for liming recommendation for sorghum cultivation in Low Humic Gley soils with high levels of organic matter.